Solid Waste Handling Techniques on Board Cargo Ships - Zakri, Yan; Anshari, Andi Imran (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objectives to be achieved in this study are to obtain an overview of the handling and characteristics of solid waste generated by cargo ships and reduce the volume of solid waste from cargo ships, while the benefits can be input for ship owners in managing waste on board. The method used is the experimental method by making a hydraulic press machine so as to reduce the volume of waste generated from cargo ships, in addition to using the interview method to the crew of the ship. The results of the solid waste survey generated on board the cargo ship originated from the deck, bridge, engine room, crew room, saloon, stern and kitchen. There are several types of solid waste including: Food scraps, Plastic, Paper, Iron, Textile/Fabric, Glass and others. The observation of the quantity of solid waste shows that the crew produces an average of 1.6 liters of waste per day per crew. While each room or section on board the cargo ship produces an average of 25 liters of solid waste per day per room. The crew's indifference to the handling of solid waste on board is 75%, so by trying to use a press, the volume of solid waste will be reduced. In addition, the press tool designed is also very easy to operate, high effectiveness, cheap and maintenance-free. The results showed that using a press can reduce the volume of solid waste by 50% to 75%